Tinjauan Hukum Asuransi Jiwa pada Lembaga Perbankan dalam Perspektif Fikih Kontemporer - Ghozali Ghozali; Isroqunnajah Isroqunnajah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Life insurance marketed through banking institutions has become a widely used financial instrument in modern society. However, its practice has sparked legal debate among Islamic scholars, particularly regarding the potential presence of gharar, maisir, and usury (riba) in its contractual mechanisms. The differing views of contemporary Islamic jurisprudence (fiqh) on the legality of life insurance, both conventional and sharia, indicate the need for a comprehensive study that places this issue within the framework of Islamic transactions. This study aims to analyze the concept and practice of life insurance within banking institutions and review its legal status from a contemporary Islamic jurisprudence perspective. The study was conducted using a library research method by collecting data from classical and contemporary fiqh literature, fatwas from the National Sharia Council (MUI), financial authority regulations, and relevant scientific publications. The analysis was conducted descriptively and analytically to outline the legal issues and assess the conformity of life insurance practices with Sharia principles. The research results show that conventional life insurance still contains the potential for contract ambiguity and speculative elements, while sharia life insurance is considered more in line with the muamalah principle through the use of tabarru', mudharabah, or wakalah bi al-ujrah contracts. From the perspective of maqāṣid al-syarī'ah, the existence of insurance can be accepted as a form of protection for life and property as long as the mechanism is free from prohibited elements. Thus, life insurance in banking institutions can be considered valid according to Sharia if it is built on the principles of transparency, fairness, and trustworthy fund management in accordance with the provisions of contemporary jurisprudence. Keywords: Life Insurance, Banking, Contemporary Jurisprudence